Stability and Antibiofilm Efficiency of Slightly Acidic Electrolyzed Water Against Mixed-Species of Listeria monocytogenes and Staphylococcus aureus - Yan, Pianpian; Chelliah, Ramachandran; Jo, Kyoung-hee; Selvakumar, Vijayalakshmi; Chen, Xiuqin; Jo, Hyeon-yeong; Oh, Deog Hwan (Frontiers in Microbiology, 2022)
In nature environment, most microorganisms live in mixed-species biofilms, in which the metabolism and growth of organisms are different from that in single species biofilms. Adhesive bacteria and their biofilms on the surface of food processing equipment are the sources of cross contamination, leading to risk for humans. Slightly acidic electrolyzed water (SAEW) has been proposed as a novel sanitizer in food and agriculture industry. Here, we investigated the changes of the physical properties of SAEW under different conditions and the disinfection abilities of SAEW against spore-forming and non-spore-forming pathogens. Furthermore, we examined the disinfection abilities of SAEW after 12 months shelf life on a mixed-species biofilm of Listeria monocytogenes monocytogenes Scott A and Staphylococcus aureus. The results showed that SAEW achieved all kill of spore forming pathogen Bacillus cereus within 30 seconds. NaOCl and ethanol showed 2.14-7.62 CFU log/mL against bacteria. Changes in the ACC and pH of the produced SAEW were generally affected by the storage conditions. Both spore-forming and non-spore forming pathogens were not detected under treatment with 50 ppm SAEW for 5 minutes in HDPE-closed conditions throughout the whole storage period. Moreover, 25 mg/L SAEW can inactivate L. monocytogenes Scott A and S. aureus biofilm cells in approximately 2.45 and 2.57 log CFU/mL in biofilms within 5 min treatment. However, the decline of the two bacteria in the mixed-species was 1.95 and 1.43 log CFU/mL, respectively. The changes of cell membrane permeability of mixed-species biofilm under treatment with SAEW was observed by using AFM and CLSM. L. monocytogenes Scott A was found to be more sensitive to SAEW in the mixed-species biofilms cells. These findings exhibited that strong antibiofilm activities of SAEW in impairing biofilm cells membranes, decreasing cell density, and inhibiting biofilm formation, which suggests that SAEW is an excellent antibacterial agent in the food processing industries.